1995
DOI: 10.1002/1097-0142(19950201)75:3<836::aid-cncr2820750315>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral stricture as a late complication of radiotherapy for stage IB carcinoma of the uterine cervix

Abstract: Background. Ureteral stricture is a rare late complication of curative radiotherapy for carcinoma of the cervix. A retrospective study was performed to determine the incidence and latency of radiation‐induced ureteral stricture, to investigate possible contributing factors, and to compare the time course and presenting characteristics of ureteral compromise caused by late radiation injury or tumor recurrence. Methods. The records of 1784 patients with FIGO stage IB carcinoma of the cervix treated with radiothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(46 citation statements)
references
References 15 publications
0
44
0
1
Order By: Relevance
“…Radiationinduced ureteric strictures have been reported in the medical literature since the 1920s. 6 Interestingly, in 1987, Dauplat et al looked at brachytherapy radiation doses to the ureter in 16 patients treated for cervical cancer by inserting a radiopaque stent in their ureters. 7 He found that 44% of these Ureteral stricture disease patients had higher radiation doses to the ureter than the bladder or rectum.…”
Section: Discussionmentioning
confidence: 99%
“…Radiationinduced ureteric strictures have been reported in the medical literature since the 1920s. 6 Interestingly, in 1987, Dauplat et al looked at brachytherapy radiation doses to the ureter in 16 patients treated for cervical cancer by inserting a radiopaque stent in their ureters. 7 He found that 44% of these Ureteral stricture disease patients had higher radiation doses to the ureter than the bladder or rectum.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is supported by an analysis of 1784 patients with stage 1B cervical cancer who were treated with radiation and had a much lower rate of ureteral stricture (2.5% at 20 years). 26 Enteric or vesical fistulas to the bladder were uncommon (1.8%) in a series of 2096 patients with cervical cancer between 1985 and 1995, and only 1 in 4 underwent an attempted surgical repair. 27 We found that surgical treatment of cervical cancer (radical hysterectomy with or without radiation) was associated with an increased risk of stress incontinence surgery; this increased risk has also been observed after hysterectomy for benign disease 28 and in our study could be due to an increased access to surgical treatment of incontinence because of postoperative follow-up with a gynecologist as opposed to a radiation oncologist.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent cancer is the most common cause of ureteral obstruction after definitive radiation therapy of cervical cancer, and it usually occurs with in the first 5 years after treatment (6). Radiation therapy also can cause ureteral injury and stricture formation.…”
Section: Discussionmentioning
confidence: 99%